2022
DOI: 10.1039/d2cy00729k
|View full text |Cite
|
Sign up to set email alerts
|

The structural evolution of Mo2C and Mo2C/SiO2 under dry reforming of methane conditions: morphology and support effects

Abstract: The thermal carburization of MoO3 nanobelts (nb) and SiO2-supported MoO3 nanosheets under a 1 : 4 mixture of CH4 : H2 yields Mo2C-nb and Mo2C/SiO2. Following this process by in...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Prior studies have reported that molybdenum oxycarbide (Mo 2 C-O) which forms under operating conditions can enhance the observed RWGS activity. 30,34,82,83 The formation of Mo 2 C-O is thought to arise from the interaction of CO 2 with Mo 2 C which forms CO and the oxycarbide phase. The Mo 2 C-O can then be reduced by H 2 to regenerate the Mo 2 C surface with the concomitant formation of water.…”
Section: Catalysis Science and Technology Papermentioning
confidence: 99%
“…Prior studies have reported that molybdenum oxycarbide (Mo 2 C-O) which forms under operating conditions can enhance the observed RWGS activity. 30,34,82,83 The formation of Mo 2 C-O is thought to arise from the interaction of CO 2 with Mo 2 C which forms CO and the oxycarbide phase. The Mo 2 C-O can then be reduced by H 2 to regenerate the Mo 2 C surface with the concomitant formation of water.…”
Section: Catalysis Science and Technology Papermentioning
confidence: 99%
“…14 Methane dry reforming (MDR) is a highly endothermic reaction; thus, high operation temperature is needed from a thermodynamic standpoint. [15][16][17][18][19] Therefore, the catalyst must have sintering resistance under high-temperature conditions. In general, catalysts used for MDR include precious metal catalysts, such as Ru, Rh, Pt, etc., [20][21][22][23][24][25][26] and transition metal catalysts containing mainly nickel.…”
Section: Introductionmentioning
confidence: 99%